Comparison of proliferating cell nuclear antigen (PCNA) staining and BrdUrd-labelling index under different proliferative conditions in vitro by flow cytometry - Lohr, Frank; Wenz, Frederik; Haas, S.; Flentje, Michael (Cell proliferation, 1995)
PC10 is a monoclonal antibody against proliferating cell nuclear antigen (PCNA). The staining pattern in immunochemistry depends on fixation and detergent extraction treatment. The aim of this study was to validate the flow cytometric PCNA assay against Bromodeoxyuridine-labelling index (BrdUrd-LI) under different proliferative conditions in vitro. Expression of PCNA in methanol fixed cells with, and without, prior detergent extraction with EDTA/Triton was compared to BrdUrd-labelling index in NIH-3T3 fibroblasts and human Caski tumour cells in exponential phase and under confluent conditions. Serum stimulation and serum starvation conditions were studied. The results for BrdUrd-LI and PCNA-index after extraction showed good correlation for 3T3 fibroblasts and for Caski cells, with some differences for serum withdrawn Caski cells. There was no correlation between the number of cells that were positive for PCNA without extraction and BrdUrd-LI. Spheroid cells with G1-DNA-content showed an almost synchronous recruitment and progression through the cell cycle after trypsination and replating. Tightly bound PCNA paralleled this synchronicity whereas total PCNA did not change significantly. The results demonstrate that immunochemical detection of non-extractable PCNA-index gives similar results as compared with BrdUrd-labelling index under different proliferative conditions in vitro for different monolayer cell lines, whereas without extraction PCNA does not correlate with BrdUrd-LI in these fast growing cell lines due to its long half-life. PCNA expression parallels the progression through the cell cycle in V79 spheroids, a primitive model of tumour growth.